The Effect of Electronic Word of Mouth (EWOM), Brand Image, and Customer Trust on Purchase Decisions at Sweet and Tiers Cake in Denpasar - I Gusti Agung Chintya Anindya Mantara; I Wayan Gede Antok Setiawan Jodi; I Made Surya Prayoga (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
The purpose of this study is to analyze the extent to which Electronic Word of Mouth (EWOM), brand image, and customer trust influence purchasing decisions at Sweet and Tiers Cake Denpasar. The phenomenon of sales fluctuations at this company is influenced by a lack of EWOM activity on social media, a brand image perceived as inconsistent in product quality and variety, and customer concerns regarding the pre-order system, which can lower consumer trust levels. This study employs a quantitative method using a multiple linear regression approach. Data were collected through a questionnaire distributed to 112 respondents, namely customers of Sweet and Tiers Cake Denpasar. The independent variables examined are Electronic Word of Mouth (EWOM), brand image, and customer trust, while the dependent variable is purchasing decisions. The findings indicate that Electronic Word of Mouth (EWOM), brand image, and customer trust have a positive and significant impact on purchase decisions. These findings demonstrate that positive reviews, a strong brand image, and high levels of customer trust can enhance purchase decisions at Sweet and Tiers Cake Denpasar.